Bacteriological Quality of Table Eggs in Moroccan Formal and Informal Sector - Fatima Zahra El Ftouhy; Saâdia Nassik; Sabrine Nacer; Ahlam Kadiri; Nadia Charrat; Kawtar Attrassi; Asma Fagrach; Mohammed Amine Bahir; Sophia Derqaoui; Abdelaziz Hmyene (International Journal of Food Science)
Eggs constitute an important part of the Moroccan diet. However, contaminated eggs can cause a serious public health problem if consumed undercooked, uncooked, or used in unpasteurized egg foodstuffs. This study was carried out to evaluate the microbial contents of eggs according to their sales sector in Morocco. For that, a total of 1770 eggs were collected from January to September 2021 from formal markets (refrigerated eggs from large shopping centers) and informal markets (eggs at ambient temperature from ambulatory sellers, street vendors, kiosks, and neighborhood stores) and transferred to the Avian Pathology Unit at Hassan II Agronomic and Veterinary Institute. The eggshells and their contents were tested separately; swabs of eggshells were used to inoculate Mac-Conkey agar, while the egg contents were cultured on Mac-Conkey and Mannitol salt agar, then standard microbiological tests were performed to identify the isolated organisms. The results showed that informal eggs were more contaminated (87%) than formal eggs (48) (p<0.05). The bacteria isolated from the eggshells (informal and formal) were Enterobacter agglomerans (59% and 21%), Klebsiella spp. (24% and 4%), Enterobacter cloacae (17% and 8%), E. coli (9% and 1%), Serratia spp. (9% and1%), Pseudomonas aeruginosa (9% and 1%), Shigella spp. (5% and 0%), Salmonella enteritidis (0% and 2%), Proteus spp. (4% and 0%), Enterobacter sakazakii (2% and 0%), Rahnella aquatilis (1% and 0%), and Staphylococcus aureus (0% and 1%). For the egg-contents, the detected bacteria (informal and formal) were Enterobacter agglomerans (14% and 28%), Klebsiella spp. (7% and 6%), Staphylococcus aureus (6% and 1%), Enterobacter cloacae (4% and 4%), E. coli (4%, 1%), Shigella spp. (4%, 0%), Acinetobacter baumannii (3% and 1%), Salmonella enteritidis (2% and 0%), Serratia spp. (1% and 6%), Proteus spp. (1% and 3%), and Enterobacter sakazakii (1% and 0%). We conclude that eggs might be contaminated with several bacteria and can constitute a public health threat in Morocco.